Israeli Territorial Annexation in Occupied Palestinian Territory: The Ambivalence of International Law - Aasi, Joni (Yuridika, 2022)
The enactment of Israeli policy on the occupied Palestinian territory has shown the development of the annexation of Israel”from the "de facto” annexation, which seized and occupied the Palestinian territory, to "de jure” annexation by enacting legislations. The dispute between these two entities arises the question of the role of international law, including the position of international law in protecting the right to self-determination and sovereignty of the annexed Palestinian territory. Hence, it is crucial to understand the Israeli practice in the matter of territorial annexation to picture the legal framework provided under international law regarding such issue, within the historical and legal context of the Palestinian case. This research argues that the international law is ambivalent. While many United Nations resolutions and legal scholars, including the advisory opinion of the International Court of Justice, have concluded the wrongfulness of the annexation of the Palestinian territory, the recognitions of other states and the difficulty in requesting state responsibility disable the access of Palestinians to justice. As such, it is necessary to focus on the tools provided by the international criminal law to prosecute war criminals and perpetrators of crimes against humanity against the Palestinian people from the Israeli political and military elites.